(3GdJehjd GdESdGej ef Gdabg Gdi GdJWHjb GdeYGUQ dOi GdHfhc GdESdGejI (B/s - (3eSOhQ, aGQSs ((3GdLRGFQ(B: s (3OGQ gheI(B, s, 2007)
(3jVe ETcGdjI GdahGFO GdeUQajI, GdHfhc GdESdGejI hNOeGJgG, GdJehjd HGdeTGQcGJ dOi GdHfhc GdESdGejI, GdJehjd HGdHjY hGdEjLGQ dOi GdHfhc GdESdGejI, GdQbGHI GdeUQajI hGdTQYjI Ydi GdHfhc GdESdGejIs
(3GdeQGLY U(B.261s
Keywords: (3GdHfhc GdESdGejIs; (3GdJehjds; (3GdJehjd GdeUQajs